Retaining vets in farm animal practice: a cross‐sectional study. (20th June 2015) - Adam, K.; Baillie, S.; Rushton, J.
Abstract : Concerns have been raised about a potential shortage of farm animal vets in the UK. There is no apparent lack of new graduates willing to work with farm animals, but practices report difficulties in recruiting and retaining experienced farm animal vets. Retention of vets in farm animal practice has been identified as a key issue for the sustainability of veterinary businesses and livestock health. A cross‐sectional study design was used to identify factors associated with vets remaining in farm animal practice. Data were collected via an online questionnaire covering employment, education, personal background and future plans. The target population was vets with experience of farm animal work in the UK. 380 responses were included in the analysis. Working in a practice where accommodation was provided and an increasing number of years since graduation were associated with significantly lower odds of remaining in farm animal practice, while working in a practice where staff appraisals were carried out; coming from a family with a commercial farm; spending more time on farm work and being on call with an experienced vet in the first job after graduation increased the odds of remaining in farm work. Gender was not significantly associated with retention.